Entropy driven winds: outflows and fountains lifted gently by buoyancy - Keller, Benjamin W.; Kruijssen, Diederik; Wadsley, James W. (Monthly notices of the Royal Astronomical Society, 2020)
We present a new theoretical framework for using entropy to understand how outﬂows driven by supernovae are launched from disc galaxies: via continuous, buoyant acceleration through the circumgalactic medium (CGM). When young star clusters detonate supernovae in the interstellar medium (ISM) of a galaxy, they generate hot, diﬀuse bubbles that push on the surrounding ISM and evaporate that ISM into their interiors. As these bubbles reach the scale height of the ISM, they break out of the disc, rising into the CGM. Once these bubbles break out, if they have suﬃciently high entropy, they will feel an upward acceleration, owing to a local buoyant force. This upward force will accelerate these bubbles, driving them to high galactocentric radii, keeping them in the CGM for > Gyr, even if their initial velocity is much lower than the local escape velocity. We derive an equation of motion for these entropy-driven winds that connects the ISM properties, halo mass, and CGM proﬁle of galaxies to the ultimate evolution of feedback-driven winds. We explore the parameter space of these equations, and show how this novel framework can explain both self-consistent simulations of star formation and galactic outﬂows as well as the new wealth of observations of CGM kinematics. We show that these entropy-driven winds can produce long wind recycling times, while still carrying a signiﬁcant amount of mass. Comparisons to simulations and observations show entropy-driven winds convincingly explain the kinematics of galactic outﬂows.
Gesehen am 04.06.2020